Evaluation of the agronomic and economic performances of integrated rice-fish systems in Mali - Akpoffo, Marius A; Guindo, Jonathan; Dossou-Yovo, E.R (2024)
"This study aimed to evaluate the agronomic and economic performances of integrated rice-fish systems in Mali. To this end, a 2-year field experiment was conducted on 3 sites including Baguineda, Selingue and in Massala in 2023 and 2024. The study included 6 treatments such as T1. Rice monoculture without fertilizer application; T2. Conventional fish monoculture; T3. Rice monoculture with fertilizer application at the recommended rate; T4. Rice monoculture irrigated using water from the fishpond; T5. Rice plot with a fishpond in the middle and T6. Rice plot with a fishpond in the border. The results showed that without fertilizer application, in year 1, paddy yield under the integrated rice-fish systems especially T4 and T5 were statistically similar to that of the conventional rice monoculture (6.88 t.ha-1; 6.75 t.ha-1 and 7.21 t.ha-1 respectively) while in year 2, the yield under T5 (6.51 t.ha-1) was significantly lower than under T3 (7.39 t.ha-1). Likewise, in year 1, fish yield under T5 and T6 were similar to under T2 (5.58, 4.34 and 5.22 t.ha-1 respectively). T5 resulted in the higher SPE (0.2 t.ha-1.day-1) and the best net benefit (13466 USD.ha-1). We concluded that integrated rice-fish systems especially T5 (with a fishpond in the middle of the plot) could be promoted as a promising rice-based farming system that enhance soil fertility, water and land use efficiency and thereby farmer income."